A protocol for a systematic review into consumers’ attitudes, beliefs and perceived ethical obligations towards farm animal welfare - Clark,Beth; Stewart,Gavin B; Panzone,Luca A; Frewer,Lynn J (PeerJ PrePrints, 2014)
This article outlines a protocol for a systematic review into consumer attitudes, beliefs and perceived ethical obligations towards farm animal welfare, utilizing both the Theory of Reasoned Action and the Theory of Planned Behavior. A number of secondary objectives will also be explored in relation to the heterogeneity within the data relating to a number of variables known to vary within existing data including; animal species, welfare measures, socio-demographic and socio-economic characteristics. The protocol outlines the rationale, objectives, inclusion criteria, search strategy and screening processes for the meta-analysis, and the plans for data extraction, risk of bias and data synthesis.
Keywords: systematic review; consumers; attitudes; beliefs; perceived ethical obligation; farm animal welfare; theory planned behaviour; theory reasoned action